Cigarette smoking, alcohol consumption and risk of systemic lupus erythematosus. (May 2014) - Takvorian, SU; Merola, JF; Costenbader, KH
Systemic lupus erythematosus (SLE) is a complex multisystem autoimmune disease whose pathogenesis is thought to involve both genetic and environmental factors. It is possible that common environmental exposures, such as cigarette smoking and alcohol consumption, might modify risk of disease development in certain individuals. Here we aim to review the epidemiologic evidence related to the association of cigarette smoking, alcohol consumption and the risk of developing SLE. A growing body of evidence suggests that cigarette smoking confers a short-term increased risk of SLE in genetically susceptible individuals. On the other hand, alcohol consumption in moderate doses may have a protective effect against the development of SLE, although this is still debated. We also have reviewed proposed mechanistic explanations underlying the role of cigarette smoking and alcohol consumption in SLE pathogenesis.